Design of a Cryptographic System for Communication Security using Chaotic Signals. (27th May 2021) - Leu, Jai-Houng; Sun, Jung-Kang; Chen, Ho-Sheng; Huang, Chong-Lin; Qiao, Dong-Kai; Lan, Tian-Syung; Chen, Yu-Chih; Su, Ay
Abstract : Disturbance or corresponding errors of the transmission of information affect the ability of error detection. The chaotic encryption system prevents errors and secures the transmission system safely. The security assures by updating chaotic signals with the parameters of the chaotic circuits which are frequently changed. The data decipher and the encryption by the chaotic signaling system renews and changes the initial condition of a chaotic electric circuit. When most of the decimal portions are less than the threshold, the transmission is accepted, and all the noninteger numbers are rounded to their nearest integers. The criterion allows the error-detection function in the security system that is proposed in this paper. The chaotic encryption system for information is applied to public channels by the authorized individual. Three pictorial examples transmitted in the proposed system successfully demonstrate the security and performance. The new system provides high efficiency in the satellite communication network.